Understanding What Drives Green Choices: A Study on Consumer Intentions to Purchase Luxury Electric Vehicles - Ginting, Nencilia Agita; Laksmidewi, Dwinita (International Journal of Environmental, Sustainability, and Social Science, 2026)
Electric vehicles (EVs) are increasingly recognized as an important solution to address environmental challenges and reduce carbon emissions. This study explores the factors influencing consumers' green purchase intention toward luxury electric vehicles in Indonesia, focusing on the roles of environmental performance, price value, range confidence, and environmental concern, with attitude toward electric vehicles serving as a mediating variable. The research sample consists of individuals who currently own gasoline-powered luxury vehicles. Using a survey method, this quantitative research measured key constructs with a Likert scale and analysed the relationships among variables through statistical testing, including validity, reliability, and structural equation modelling. The results show that environmental performance, price value, range confidence, environmental concern, and attitude toward electric vehicles all have a significant impact on green purchase intention. Moreover, the four main variables also significantly influence attitudes toward electric vehicles. The study further confirms that attitude toward electric vehicles fully mediates the effects of environmental performance, price value, range confidence, and environmental concern on green purchase intention.